ANALISIS STRATEGI PENGEMBANGAN WADUK KUBANGKANGKUNG SEBAGAI DESTINASI WISATA UNGGULAN CILACAP - Alvionita, Agnes; Pertiwi, Elva Dian (Kepariwisataan: Jurnal Ilmiah, 2020)
Cilacap is one of the districts in Central Java that has tourism potential with various tourism destination. One of them is Waduk Kubangkangkung. This Waduk Kubangkangkung is a tourism destination that offers beautiful natural tourism and also attractive tourism attraction. The purpose of this study was to determine the role of the local community in Waduk Kubangkangkung development, knowing the manager‘s efforts in developing Waduk Kubangkangkung as a sustainable tourism destination, and finding the development strategy of Waduk Kubangkangkung to attract tourists . While the method used in this research is descriptive qualitative method and SWOT analysis. The results of this study are the need for collaboration between managers and other stakeholders towards Waduk Kubangkangkung, improve promotion and also facilities that needed by tourists. Keywords: Tourism Development, Tourism Destination, Management